Anxiety Influences the Perceptual-Motor Calibration of Visually Guided Braking to Avoid Collisions. Issue 3 (4th May 2019) - Ruginski, Ian T.; Thomas, Brandon J.; Geuss, Michael N.; Stefanucci, Jeanine K.
ABSTRACT: We investigated whether anxiety influences perceptual-motor calibration in a braking to avoid a collision task. Participants performed either a discrete braking task (Experiment 1) or a continuous braking task (Experiment 2), with the goal of stopping before colliding with a stop sign. Half of participants performed the braking task after an anxiety induction. We investigated whether anxiety reduced the frequency of crashing and if it influenced the calibration of perception (visual information) and action (brake pressure) dynamically between-trials in Experiment 1 and within-trials in Experiment 2. In the discrete braking task, anxious participants crashed less often and made larger corrective adjustments trial-to-trial after crashing, suggesting that the influence of anxiety on behavior did not occur uniformly, but rather dynamically with anxiety amplifying the reaction to previous crashes. However, when performing continuous braking, anxious participants crashed more often, and their within-trial adjustments of deceleration were less related to visual information compared to controls. Taken together, these findings suggest that the timescale and nature of the task mediates the influence of anxiety on the performance of goal-directed actions.